Protection and Legal Liability of Electronic Medical Records in Primary Clinics from the Perspective of Legal Certainty - Novianti Novianti; Abdul Kolib; Handar Subhandi Bakhtiar (Asian Journal of Social and Humanities, 2023)
One of the functions of Law Number 29 of 2004 concerning Medical Practice is the regulation of medical records. Along with the changing times, medical records have also developed into electronic medical records. Electronic medical records become a record of the patient's health during his life so that a need for protection and legal liability of electronic medical records at Pratama clinics. This study aims to analyze the law on the protection and legal liability of electronic medical records at Pratama clinics in terms of legal certainty perspective. This research uses normative empirical with a juridical normative research approach. Meanwhile, the research analysis is quantitative analysis. The results showed that medical records are regulated in Article 47 of the 2004 law on medical practice. Along with the development of technology comes Electronic Medical Records (RME) where documentation of patient medical records throughout life in electronic form. The implementation of electronic medical records in this Pratama clinic can provide better legal certainty for all parties involved in the health care process.